The Impact of Language and Communication Barriers and Family Influences to Marital Instability: Perspectives on Intercultural Marriage - Maizura Abd Rashid, Intan; Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza; Harith Amlus, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Communication is essential to the life of the conjugal association. Successful communication is multifaceted and created through time and encounters. Companions concurred that their correspondence with each other had changed throughout the years dependent on their obtained learning about themselves, just as their mate. Having a comprehension of the essential language and correspondence styles of each other is critical to intercultural marriages. Intercultural marriage unions are energizing marvels in this day and age. The essence of cozy connections is changing. As people wed one who is socially diverse, they comprehend that they will experience new difficulties, developing torments, and undertakings. Conflict will erupt. Goals and conjugal fulfillment can be achieved. Despite the assorted variety of values, norms, objectives, and correspondence styles, an establishment of affection is fundamental to the improvement of conjugal fulfillment in intercultural relational unions. This investigation, among others, proposes it is attainable and gives important understanding into how people from different societies who wed each other with the desire for suffering adoration can have fulfillment for a lifetime.